Negative thermal expansion of HTSC-type structures: low temperature structure measurements on Eu₁₊x(Ba₁₋yRy) ₂₋xCu₃O₇₋d compounds and theoretical treatment - Eremenko, V.V.; Feodosyev, S.B.; Gospodarev, I.A.; Sirenko, V.A.; Shvedun, M.Yu.; McCallum, W.; Tovar, M. (Физика низких температур, 2005)
The temperature dependences of the lattice parameters were investigated on the perovskite-like structures Eu₁₊x(Ba₁₋yRy) ₂₋xCu₃O₇₋d with Ba substitution by light rare earth, using x-ray diffraction techniques. A negative thermal expansion effect was observed and explained in detail.